2011
DOI: 10.3945/ajcn.110.003426
|View full text |Cite
|
Sign up to set email alerts
|

Folate and cobalamin status in relation to diet in healthy 2-y-old children

Abstract: Background: Limited data exist on sources of folate and cobalamin in the toddler diet. Objective: We examined the influence of diet on folate and cobalamin status in healthy toddlers in an unfortified population. Design: Dietary intake was assessed in 178 children, aged 24 mo, by using 7-d food records and related to serum folate and cobalamin status in 155 children. Results: Median (25th-75th percentile) daily intakes of folate and cobalamin were 87 lg (74-104 lg) and 3.1 lg (2.4-3.8 lg), respectively. Thirty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
36
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 28 publications
(36 reference statements)
7
36
2
Order By: Relevance
“…When folate status is low or deficient, elevated plasma homocysteine is invariably observed (McNulty and Scott, 2008), but this marker is not specific for folate and may also be affected by changes in status of cobalamin and pyridoxine. (Hay et al, 2011). In the fifth study, serum folate concentrations reported as P5-P95 were 23 to 120 nmol/L in infants at the age of six months, 16 to 72 nmol/L in infants aged 12 months and 9 to 46 nmol/L in children at the age of two years (Hay et al, 2008).…”
Section: Folatementioning
confidence: 98%
“…When folate status is low or deficient, elevated plasma homocysteine is invariably observed (McNulty and Scott, 2008), but this marker is not specific for folate and may also be affected by changes in status of cobalamin and pyridoxine. (Hay et al, 2011). In the fifth study, serum folate concentrations reported as P5-P95 were 23 to 120 nmol/L in infants at the age of six months, 16 to 72 nmol/L in infants aged 12 months and 9 to 46 nmol/L in children at the age of two years (Hay et al, 2008).…”
Section: Folatementioning
confidence: 98%
“…In a systematic review on the associations between cobalamin intake and biomarkers in children (Iglesia et al, 2013), one cross-sectional study was identified which examined dietary intake of cobalamin and serum cobalamin, holoTC, MMA and tHcy concentrations in 155 healthy, non-breastfed Norwegian toddlers at 24 months of age (Hay et al, 2011). Seven-day weighed food records were used for cobalamin intake assessment.…”
Section: Infants and Childrenmentioning
confidence: 99%
“…Data on nutrient intakes and biochemical status in young children aged 12-36 months from 19 countries were reviewed by the expert group [17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41]. They are obtained from both national surveys and cross-sectional community-based surveys in Asia (Bangladesh, India, Indonesia, Malaysia, People's Republic of China, Philippines, Thailand and Vietnam), Australia, New Zealand, Europe (France, Ireland and Norway), Africa (Cameroon and South Africa), North America (Canada, Mexico and USA) and South America (Brazil).…”
Section: Nutrient Intakes and Status Of Young Children Aged 12-36 Monthsmentioning
confidence: 99%